Social media and security in Kenya Reports, 2015-2017 - Molony, Thomas (UK Data Service, 2022)
SMS:Africa provides evidence-based research on the role social media can play in shaping relationships between technology, power and the dynamics of democracy. It maps how both those charged with community safety and non-state actors are using social media in a security context, developing an understanding of how their actions reflect on the nature of ICT and their ability to re-cast power relations, (in)security and democracy in fragile states. As more people connect to social media in Africa, their expectations for real-time information are changing, especially in terms of security. This is leading those charged with community safety to alter their ways of interacting with the public, posing new challenges concerning the rapid flow of (mis)information. At the same time, social media creates opportunities for security sector agencies to engage more directly with the public in providing information, and potentially offers new prospects for improved cooperation in enhancing community safety. The project examines two variations of insecurity in Africa: sustained threats, and anticipated times of increased insecurity. Kenya is the case for sustained insecurity due to recent terrorist attacks and a threat of future attacks. Sierra Leone and Tanzania are cases in which there is an expected heightened risk of instability due to elections. Additionally, it examines whether lessons learnt from Kenya's exceptionally high use of social media in a security context could be applied to other countries where social media is in its infancy. The collections consists of fortnightly reports analysing security-related discussions on social media relating to Kenya. The project aims to provide a timely understanding of the role social media plays in documenting and driving (in)security in East and West Africa. As more people connect to social media in Africa, their expectations for real-time information is changing, especially in terms of security. This is leading those charged with community safety to alter their ways of interacting with the public, posing new challenges concerning the rapid flow of (mis)information. At the same time it creates opportunities for security sector agencies to engage more directly with the public in providing security-related information, and potentially offers new prospects for an improved cooperative relationship in enhancing community safety. The project works towards the goal of reducing the insecurity that contributes to poverty. It corresponds to question 3 of the call concerning measures that can be taken to reduce the risks and impact of violence and instability that affect the poor. We have 4 research questions 1) Who are the key stakeholders in relation to social media and security in the case study countries, and who is being excluded? 2) How is social media being used by authorities responsible for community safety to reduce the risks and impact of violence and instability? 3) In what ways can social media be used to increase security or perceptions of security? 4) How can social media serve as an early warning of tensions that threaten security? We use a mixed methodology uncommon to research in Africa, combining traditional qualitative data collection methods (focus groups, interviews) with social media monitoring. This involves unique engagement with individuals/institutions who are actively using social media in a security context, as well as traditionally excluded groups. It goes beyond analysing posted messages to consider how these messages are perceived, with a view to gaining insight into the effectiveness (both intended and unintended consequences) of social media in the security setting. Social media monitoring software complements the other research methods by allowing real-time access to data relating to unanticipated security incidents (ie, a terrorist attack). We will examine two variations of insecurity in Africa: sustained threats, and anticipated times of increased insecurity. Kenya will be the case for sustained insecurity due to recent terrorist attacks and a threat of future attacks. Sierra Leone and Tanzania will be cases in which there is an expected heightened risk of instability due to elections. Additionally, we will examine whether lessons learnt from Kenya's exceptionally high use of social media in a security context could be applied to other countries where social media use is in its infancy. The project will benefit 1) policymakers and authorities responsible for community safety (security services, national electoral bodies, political leaders) 2) non-state actors using social media to shape debates around security (civil society groups; prominent cyber-activists; 'citizen journalists') 3) UK government agencies involved in security and development 4) academic researchers engaging with policymakers regarding security and/or those interested in new research methodologies. These groups all have a role to play in ensuring that the ultimate beneficiaries are poor and vulnerable communities who so often bear the brunt of violence and insecurity. We will provide evidence-based research on the role social media can play in shaping the relationship between technology, power and the dynamics of democracy. We will map how both those charged with community safety and non-state actors are using social media in a security context, and will develop an understanding of how their actions reflect on the nature of ICT and their ability to re-cast power relations and (in)security and democracy in fragile states. From this we will offer recommendations for best-practices on the use of social media in a security context.